Reliable recording and analysis of multimedia collaboration sessions over wireless networks - Lambrinos, Lambros (My University, 2005)
The increasing popularity of multi-way multimedia collaboration sessions over wired networks is now spreading into the wireless domain. Due to this, the inherent need to record some sessions and make them available for later replay poses some new interesting challenges. This paper presents an analysis of the recording requirements and issues arising when participants "based" on a wireless network are also present in a session. An architecture for supporting reliable recording of Voice-Over-IP sessions is described; an inherent part is an agent on the sender host that assists in the recording process. Reliability is facilitated through a flexible and adaptive data repair protocol. Once a recording is complete, it can be used to analyse the session and assist in locating any network and reception problems that may have degraded the quality of the conversation. Moreover, playing back the recorded session will potentially provide better quality than what the participants observed if there was packet loss during the conversation.
Keywords: Computer architecture; Wireless telecommunication systems; Multimedia systems